2016
DOI: 10.1377/hlthaff.2016.0140
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Care Program Reduces Disability And Promotes Aging In Place

Abstract: The Community Aging in Place, Advancing Better Living for Elders (CAPABLE) program, funded by the Center for Medicare and Medicaid Innovation, aims to reduce the impact of disability among low-income older adults by addressing individual capacities and the home environment. The program, described in this innovation profile, uses an interprofessional team (an occupational therapist, a registered nurse, and a handyman) to help participants achieve goals they set. For example, it provides assistive devices and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
164
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(167 citation statements)
references
References 19 publications
3
164
0
Order By: Relevance
“…This is evident in recent research on a 5‐month Medicare and Medicaid demonstration project called CAPABLE (the Community Aging in Place, Advancing Better Living for Elders program), which delivered care at home to 281 adults aged 65 years and older from 2012 to 2015, via visits from an occupational therapist (six visits), a nurse (four visits), and a handyman (one all‐day visit). They found this interprofessional care improved activities of daily living and promoted aging in place . Another recent study found integration of HCBC services and providing LTSS at Independence at Home (IAH) demonstration sites for frail, older nonveteran adults delayed the need for long‐term institutionalization .…”
Section: Discussionmentioning
confidence: 99%
“…This is evident in recent research on a 5‐month Medicare and Medicaid demonstration project called CAPABLE (the Community Aging in Place, Advancing Better Living for Elders program), which delivered care at home to 281 adults aged 65 years and older from 2012 to 2015, via visits from an occupational therapist (six visits), a nurse (four visits), and a handyman (one all‐day visit). They found this interprofessional care improved activities of daily living and promoted aging in place . Another recent study found integration of HCBC services and providing LTSS at Independence at Home (IAH) demonstration sites for frail, older nonveteran adults delayed the need for long‐term institutionalization .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, proven geriatric models of care have already been successfully delivered to vulnerable middle-aged adults (43, 44). Novel models of care that improve functioning in low income older adults (45) may hold similar promise for low income adults in middle age.…”
Section: Discussionmentioning
confidence: 99%
“…Existing depression treatment studies targeted to the homebound population have rarely addressed these comorbidities (Bruce et al, 2015; Choi et al, 2014; Ell et al, 2007). The Community Aging in Place, Advancing Better Living for Elders (CAPABLE) intervention is one of the handful of interventions that simultaneously address multiple domains of functional limitations (Szanton, Leff, Wolff, Roberts, & Gitlin, 2016). Preliminary analyses showed that depressive symptoms improved in 53% of the CAPABLE participants at 5-month follow-up.…”
Section: Discussionmentioning
confidence: 99%